Evaluation of the killing effects of UV254 light on common airborne porcine viruses - YingWu Qiu; YingWu Qiu; QunHui Li; WenKai Zhao; Hao Chang; Hao Chang; JunHua Wang; Qi Gao; Qi Gao; Qingfeng Zhou; GuiHong Zhang; GuiHong Zhang; et al. (Frontiers in Veterinary Science, 2025)
UV exposure is a common method of disinfection and sterilization. In the present study, the parallel beam test was performed to collect fluids containing infectious viruses using a parallel beam apparatus after UV254 irradiation (0, 0.5, 1, 3, 5, 7, 10, or 20 mJ/cm2). The air sterilization test was performed by irradiating the air in the ducts with UV254 light (0, 1, 2, 3, 4, or 6 mJ/cm2) to collect airborne particles containing viruses through the air sterilization equipment. Furthermore, viral inactivation was assessed based on cytopathic effect (CPE) detection and immunofluorescent assays (IFA). Both the CPE and immunofluorescence signal intensity decreased as the UV254 dose increased. The UV254 doses required to inactivate ASFV (107.75 copies/mL), PRRSV (106.29 copies/mL), and PEDV (107.71 copies/mL) in the water were 3, 1, and 1 mJ/cm2, respectively. The UV254 dose required to inactivate ASFV (104.06 copies/mL), PRRSV (103.06 copies/mL), and PEDV (104.68 copies/mL) in the air was 1 mJ/cm2. This study provides data required for biosecurity prevention and control in swine farms.